Establishment of embryo transfer in the musk shrew (Suncus murinus) - Naoko INOUE; Akinori HOTTA; Teppei GOTO; Masumi HIRABAYASHI; Yoshihisa UENOYAMA; Hiroko TSUKAMURA (The Journal of Reproduction and Development, 2022)
The present study established techniques to induce pseudopregnancy, in vitro oocyte cultures from pronuclear to 2- to 4-cell stages, and embryo transfer in musk shrews, a reflex ovulator. Offspring were subsequently obtained by transferring in vivo-developed or in vitro-cultured embryos. Female musk shrews received human chronic gonadotropin (hCG), with or without mating stimuli, from vasectomized males to produce pseudopregnant recipients. Embryos at the 2- to 4-cell stage were collected 44–48 h after mating. Another set of embryos was collected 26–27 h after mating and then cultured for 20 h from the pronuclear to 2- to 4-cell stages. Subsequently, embryos were transferred into the oviducts of pseudopregnant recipients 24 or 48 h after the induction of pseudopregnancy. Offsprings were successfully obtained from recipients that received hCG 24 h before embryo transfer, regardless of mating stimuli. These techniques may be valuable for producing transgenic musk shrews.